A Technology of Ball Dribbling Teaching in Basketball - Лаврін, Г. З. (Physical Education Theory and Methodology, 2015)
The paper outlines a technology developed for teaching ball dribbling in basketball illustrated in a flow chart. It defines the main prerequisites for acquisition of the game technique, establishes the system of specific tasks and selects the means to solve them, determines the typical mistakes and ways to prevent and eliminate them, offers some means of control and self-control.